Penerapan Breastfeeding Father dalam Meningkatkan Produksi ASI Pada Ibu Post Partum Sectio Caesarea - Salahudin, Eka Riswanty Maharani; Syrilla Da Cunha, Theresia; Riske Wijayanti, Anggia (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Breastfeeding is a natural process that provides benefits for both mother and baby. However, post partum sectio caesarea mothers often experience various challenges in breastfeeding, such as surgical wound pain and lack of support, which can affect breast milk production. One effort to improve breast milk production is through the implementation of breastfeeding father, which refers to the involvement of the father in providing emotional, informational, and instrumental support to the mother. The purpose of this study is to describe maternity nursing care through the implementation of breastfeeding father in increasing breast milk production among post partum sectio caesarea mothers in the Anggrek Ward of RSUD dr. T.C. Hillers Maumere. The method used in this study is descriptive with a case study approach involving two post partum sectio caesarea mothers who experienced problems with breast milk production. The intervention provided included education and involving the husband in supporting the breastfeeding process. The results showed that after the implementation of breastfeeding father, there was an increase in breast milk production, indicated by smoother milk flow, increased breastfeeding frequency, and signs of adequate milk intake in the baby. In addition, both mothers showed increased confidence in breastfeeding. In conclusion, the implementation of breastfeeding father is effective in increasing breast milk production among post partum sectio caesarea mothers